Pemberdayaan Santri dalam Pemanfaatan Limbah Kayu Bangunan sebagai Souvenir di Pondok Pesantren Miftahul Mubtadiin Ar-Ridlo Krempyang Nganjuk - Masduqi Masduqi; Siti Maryam Qurotul Aini; Ahmad Mustakim; Idam Mustofa (Janaka, Jurnal Pengabdian Masyarakat, 2022)
Utilization of building wood waste as souvenirs at the Miftahul Mubtadiin Ar-Ridlo Islamic boarding school has been attempted in the santri empowerment program. The approach used is Asset Based Community Development, where the implementation team and service partners use existing assets and then develop and utilize them. Empowerment of boarding school administrators in the arts and furniture managers can show efforts to increase the capacity of cadres with the concept of No Body Has Nothing. This program can explore the smallest potential of the trainees. This is in line with the principle that every human being is born with their own strengths, no one is without potential, even if it is only the ability to smile, all have potential and all can contribute. The success of this skill dissemination proves that there has been a diffusion of educational innovation. The practice of service learning through the training carried out shows the efforts of administrators and students to cultivate their soft skills with the impact of changes, including: The emergence of new skilled cadres, the experience of the administrators in building partnerships so that they can optimize their potential and assets to develop the creativity of students in the carpentry field.